PENDIDIKAN KARAKTER UNTUK PERKEMBANGAN MORAL ANAK USIA DINI - Aisyah Aisyah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2020)
Education is a very important thing for every generation of the nation that starts early. Early childhood education is a series of systematic and programmatic efforts in conducting coaching aimed at children from birth up to the age of 6 through the provision of educational stimuli to help the child's physical and spiritual growth and development have readiness to enter further education. In early childhood education has a great purpose. The big goal is to develop the potential of children early on in preparation for life that can adapt to the environment. Early childhood character education is very important. This is in order for the child to have good moral behavior. They learn to understand the good and the bad from what they do. Environmental influences greatly influence the moral development of children such as playmates, educators and parents as well as the surrounding environment. In this case it is important for educators and parents to support the moral development of the child through the planting of good values, set an example with a good example, because the nature of the child is a good impersonator. So the child can imitate it.